2019
DOI: 10.1016/j.pmedr.2019.100962
|View full text |Cite|
|
Sign up to set email alerts
|

Gender differences in the association between modifiable risk factors and financial hardship among middle-aged and older adults

Abstract: Objective To identify associations between modifiable risk factors (cigarette smoking, alcohol consumption, and obesity) and financial hardship (difficulty paying bills, food insecurity and medication need) among middle-aged and older Americans in a nationally representative sample. Methods This was a cross-sectional study of 8212 persons age 50 years and older who completed the core 2010 Health and Retirement Study survey and the psychosocial questionnaire. We ran sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…As an important signaling pathway of innate immunity, the MAPK signaling pathway is very sensitive to the changes and metabolism of intracellular inflammatory factors. After activation, the MAPK signaling pathway plays an important role in the inflammatory response, cell proliferation, cell differentiation, apoptosis, cell invasion, and other reactions ( Sprong et al, 2004 ; Holm et al, 2010 ; Farooq, 2015 ; Marshall et al, 2019 ). In N. meningitidis -infected cells, the MAPK signaling pathway was activated and the expression of IL-6, IL-8, and TNF-α increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an important signaling pathway of innate immunity, the MAPK signaling pathway is very sensitive to the changes and metabolism of intracellular inflammatory factors. After activation, the MAPK signaling pathway plays an important role in the inflammatory response, cell proliferation, cell differentiation, apoptosis, cell invasion, and other reactions ( Sprong et al, 2004 ; Holm et al, 2010 ; Farooq, 2015 ; Marshall et al, 2019 ). In N. meningitidis -infected cells, the MAPK signaling pathway was activated and the expression of IL-6, IL-8, and TNF-α increased.…”
Section: Discussionmentioning
confidence: 99%
“…Activated p38-MAPK positively regulates the expression of many inflammation-related genes, such as those encoding TNF-α, IL-1, IL-6, and IL-8. Previous studies have shown that SB203580, as a specific inhibitor of p38, could regulate and reduce the production of proinflammatory cytokines after inhibition of p38-MAPK ( Frieling et al, 1997 ; Braun et al, 2002 ; Sprong et al, 2004 ; Li et al, 2017 ; Marshall et al, 2019 ). To verify the role of p38 in the E2 effect, we pretreated HBMECs and MECs infected with N. meningitidis with the p38 inhibitor SB203580.…”
Section: Discussionmentioning
confidence: 99%
“…The level of difficulty paying monthly bills continuous variable was measured using a 5-point Likert scale ("1" ¼ not hard to "5" ¼ very hard). This variable is commonly used as an indicator of financial hardship, as well as socioeconomic status (Marshall et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Participants who were current smokers had 1.88 greater odds of being food insecure compared to those who never smoked (OR=1.88; 95% CI: 2.54-4.43). Similarly, former smokers also had greater odds of being food insecure compared to those who had never smoked (OR=1.35; 95% CI: 1.34-2.65) (Marshall et al, 2019).…”
Section: Socioeconomic Statusmentioning
confidence: 97%